Integration of SAR, optical remote sensing data and GIS for change detection and restoration of Nipa palm plantation in Pak Phanang, Thailand - Bencure, Lannet; Tripathi, Nitin Kumar; Gallardo, Wenresti G.; Somsak Boromthanarat; Ebbers, Theo; Singhroy, Vern; Asian Development Bank - Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Assessing and improving the potential growth and production of Nipa palm is very important especially to the local people in tambon Khanap Nak whose livelihood depends mainly on Nipa palm. The objectives of this study were to assess quantitatively the change in the distribution and healthiness of Nipa palm for 16 years (1993-2009); to find suitable area for Nipa palm plantation with the following parameters: water salinity, water pH, soil salinity, soil pH, soil texture, water availability/accessibility, elevation, land use, and slope; to estimate sap, sugar, and ethanol production, and to evaluate the perceptions of the local people towards Nipa palm. The study utilized the combination of optical and SAR remote sensing data, Geographic Information Systems (GIS), and local people{u2019}s knowledge through in-depth interview. Healthiness of Nipa palm was measured according to the NDVI values of extracted Nipa palm from 1993 to 2009. The results show that there was a rapid reduction in the total Nipa palm area during 1993- 2006 that reduced the area into more than half; and there was also a decreasing pattern with the NDVI values during this period. The result also revealed that NDVI values is highly correlated to water salinity; while there was very low correlation values with rainfall. The final suitability map produced was classified into: highly, moderately, marginally, and low suitable. The results show that 41.9% of the total area of Khanap Nak was found to be highly suitable, 15.4% moderately suitable, 15.8% marginally suitable, and 20.1% low suitable. And when compared with the existing Nipa palm, it was found out that around 98% of the existing Nipa palm area fell under the highly suitable, 1.4% under the moderately suitable; 0.3% under the marginally suitable; and 0.4% under the low suitable category. Moreover, the estimated present ethanol production is more than 60 times the required ethanol for consumption in the whole Pak Phanang district. The production on sap, sugar, and ethanol will be increased in quintuple times if all highly suitable areas will be planted with Nipa palm.
A thesis submitted as partial fulfillment of the requirements for the degree of Master of Engineering in Remote Sensing and Geographic Information Systems
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Nypa palm -- Remote sensing -- Thailand -- Pak Phanang District; Nypa palm -- Geographic information systems -- Thailand -- Pak Phanang District